2012
DOI: 10.1097/rlu.0b013e3182393390
|View full text |Cite
|
Sign up to set email alerts
|

Utility of F-18 FDG PET/CT in Screening for Paraneoplastic Neurological Syndromes

Abstract: PET/CT may be a useful screening tool for patients with clinically suspected PNS who do not exhibit well-characterized paraneoplastic antibodies. Therefore, we recommended that PET/CT should be performed for patients with clinically suspicious PNS regardless of the presence of well-characterized paraneoplastic antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Indeed, previous studies have reported on the usefulness of 18 F-FDG-PET in PNS, but its accuracy seems to be related to the pre-test probability [9][10][11][12][13][14][15][16][17][18][19][20]. Nevertheless, only Vaidyanathan et al [21] evaluated PET/CT in terms of pre-test clinical probability and its relation to the final detection of malignancy.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, previous studies have reported on the usefulness of 18 F-FDG-PET in PNS, but its accuracy seems to be related to the pre-test probability [9][10][11][12][13][14][15][16][17][18][19][20]. Nevertheless, only Vaidyanathan et al [21] evaluated PET/CT in terms of pre-test clinical probability and its relation to the final detection of malignancy.…”
Section: Introductionmentioning
confidence: 94%
“…Over the last decade, more studies have investigated the application of combined 18 F-FDG PET/CT in the initial evaluation and diagnosis of paraneoplastic syndromes and occult malignancy (3,5,(14)(15)(16)(17). In our study, the subgroup analysis by imaging modality revealed that 18 F-FDG PET/CT showed a significantly higher specificity than 18 F-FDG PET alone.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study design, patient demographics and characteristics, paraneoplastic presentation, paraneoplastic antibody status, index test, proportion of patients diagnosed with underlying malignancy, and reference standards of each included study were summarized in Supplemental Tables 2 and 3 (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(28)(29)(30)(31). Among the 24 studies included in the qualitative assessment, 4 studies were prospective and 20 studies were retrospective.…”
Section: Study Characteristics and Methodologic Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations